Stability of structures : principles and applications - Yoo, Chai Hong.; Lee, Sung Chul, 1957- (Amsterdam : Elsevier, 2011)
Summary :'The current trend of building more streamlined structures has made stability analysis a subject of extreme importance. It is mostly a safety issue because Stability loss could result in an unimaginable catastrophe. Written by two authors with a combined 80 years of professional and academic experience, the objective of Stability of Structures: Principles and Applications is to provide engineers and architects with a firm grasp of the fundamentals and principles that are essential to performing effective stability analysts' -- Provided by publisher.
Includes bibliographical references (p. 514-515) and index.
Keywords: Structural stability; Safety factor in engineering